Gender Fluidity and Nonbinary Gender Identities Among Children and Adolescents. (27th April 2020) - Diamond, Lisa M.
Abstract: A growing number of children and adolescents report having gender identities or expressions that differ from their birth‐assigned gender or from social and cultural gender norms. Some identify as transgender, whereas others consider themselves nonbinary or gender fluid . Nonbinary and gender fluid youth are distinct from transgender youth in that they typically report that their gender identity (i.e., their internal sense of gender) or their gender expression (i.e., their public presentation of their gender through appearance, dress, and behavior) fall outside the traditional male–female binary. For example, nonbinary youth may identify as both male and female or neither male nor female. In this article, I discuss what we know about nonbinary forms of gender identity and expression among children and adolescents, and how these experiences converge and diverge from binary forms of the transgender experience. I also identify the most important priorities for fostering well‐being among all youth.